Recalcitrant Venous Leg Ulcers May Heal by Outpatient Treatment of Venous Disease Even in the Presence of Concomitant Arterial Occlusive Disease. Issue 3 (September 2016) - Mosti, G.; Cavezzi, A.; Massimetti, G.; Partsch, H.
Abstract : Objective/Background: Peripheral arterial occlusive disease (PAOD) is reported in about 15–20% of patients with venous leg ulcers (VLU). In such cases arterial recanalization is often recommended, and compression therapy is considered a contraindication when the ankle brachial pressure index (ABPI) is < 0.8. The aim of this study was to compare the outcome of patients with recalcitrant VLU, both without any arterial impairment ("pure venous recalcitrant leg ulcer" [pvRLU]) and with associated PAOD ("mixed arterial and venous recalcitrant leg ulcer" [mavRLU]), by treating only the venous disease. Methods: The records of 180 outpatients with recalcitrant ulcers treated between January 2011 and July 2014 were reviewed retrospectively. In total, 109 were affected by pvRLU and 71 by mavRLU, with moderate PAOD defined by an ABPI between 0.5 and 0.8. In addition to the same local wound dressing, the patients received ultrasound guided foam sclerotherapy of the refluxing superficial veins and a modified inelastic compression with a pressure ≤ 40 mmHg. No patient was referred for arterial revascularization. The patients were followed until ulcer healing. Results: Patients with pvRLU and mavRLU showed comparable demographic characteristics. Twenty-five patients were lost to follow up and the outcomes were analyzed in 93 patients with pVLU (85.4%) and in 62 patients with mavRLU (87.4%). The maximum time to complete healing was 48 weeks in the pvRLU group and 52 weeks in the mavRLU group ( p = .009), The median healing time was 23 (pvRLU) versus 25.5 weeks (mavRLU) ( p = .030). Deep venous incompetence ( p < .001), ulcer surface area ( p < .001), arterial disease ( p = .002), and ulcer duration ( p < .010) were risk factors for prolonged healing. Conclusion: Treatment of recalcitrant leg ulcers by treating venous incompetence by foam sclerotherapy and modified compression is successful, even if underlying moderate PAOD is not actively treated.